Structural and Substructural Properties of the Zinc and Cadmium Chalcogenides Thin Films (a Review) - C.J. Panchal; A.S. Opanasyuk; V.V. Kosyak; M.S. Desai; I.Yu. Protsenko (Журнал нано- та електронної фізики)
In this paper, the structural properties of the zinc and cadmium chalcogenide thin films are considered. The influence of the structural defects such as grain boundaries, dislocations, native point defects, etc., on the optical and electrical properties of the thin films was studied. The methods of the II-VI thin films deposition are described. The influence on the sub-structural properties (phase compositions, texture, grain size, stacking faults concentration, micro deformation levels, and coherent domain size) of the thin films grown by the close-spaced vacuum evaporation method was analyzed. The growth conditions of the thin films with optimized parameters have been determined.